Reimagining Vietnam’s early childhood curriculum: Moving toward competency, equity, and cultural relevance - Ngoc Minh, Ngoc Minh (Journal of Early Childhood Care and Education, 2025)
This paper analyzes the current Early Childhood Education (ECE) curriculum in Vietnam and the key innovations proposed in the Ministry of Education and Training’s (MOET) new draft curriculum. A systematic review of 42 academic papers identifies major limitations in the existing curriculum, including rigid content, outdated pedagogies, and limited alignment with 21st-century learning needs. In contrast, the draft curriculum introduces a modern, competency-based and rights-based approach that prioritizes holistic development, social-emotional learning, and respect for diversity. Its reforms center on three orientations: (1) curriculum modernization through socio-emotional competencies, child agency, and flexible pedagogical approaches; (2) strengthened teacher and institutional autonomy, including improved working conditions and increased decision-making power; and (3) equity and inclusion through rights-based practices and robust family–community engagement. These developments demonstrate Vietnam’s commitment to global ECE standards and advance international discussions on competency- and rights-based early childhood curriculum reform.